1981
DOI: 10.1111/j.1751-0813.1981.tb05767.x
|View full text |Cite
|
Sign up to set email alerts
|

THE TRANSMISSION OFBABESIA BOVISIN HERDS OF EUROPEAN AND ZEBU X EUROPEAN CATTLE INFESTED WITH THE TICK, BOOPHILUS MICROPLUS

Abstract: Transmission of Babesia bovis by the tick Boophilus microplus was studied in 4 breeding herds of European and Zebu x European cattle under different levels of tick infestation. The observations consisted of weekly counts of female ticks on the cattle, monthly serological tests for antibodies to B. bovis, examination of tick larvae from the pasture to determine B. bovis infection rates and comparison of the suitability of paddocks for tick reproduction. The rate of transmission (inoculation rate) was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Although only a third of the total cattle population surveyed demonstrated antibodies to B. boris few clinical cases of babesiosis due to B. boris infections are reported in native animals. Perhaps enhanced tick resistance (Mahoney, Wright, Goodger, Mirre, Sutherst and Utech, 1981) or a genetically based immunity to B. boris characteristic of the zebu crosses act to affect low inoculation rates of this Babesia parasite.…”
Section: Resultsmentioning
confidence: 99%
“…Although only a third of the total cattle population surveyed demonstrated antibodies to B. boris few clinical cases of babesiosis due to B. boris infections are reported in native animals. Perhaps enhanced tick resistance (Mahoney, Wright, Goodger, Mirre, Sutherst and Utech, 1981) or a genetically based immunity to B. boris characteristic of the zebu crosses act to affect low inoculation rates of this Babesia parasite.…”
Section: Resultsmentioning
confidence: 99%
“…Mahoney et al 38 compared transmission of B bovis in B taurus and in three-eighths to half B indicus crossbred cattle in southeast Queensland and concluded that, in an enviro n m e n t u n f a vourable for tick surv i val, stocking with cro s s b red cattle will over several seasons almost lead to the disappearance of the ticks. However, our results show that if such cattle are moved to a paddock with a high B microplus infestation, Babesia transmission rates can be very high.…”
Section: Parasite Typingmentioning
confidence: 99%
“…Herds with > 75% seropositivity were considered to be endemically stable (Stable herds). 19.54, P < 0.001). There was no significant difference in the likelihood of endemic stability between regions for A marginale (Chi-sq 5.02, P = 0.17).…”
Section: Discussionmentioning
confidence: 88%
“…The prevalence of infection among ticks feeding on Bos indicus cattle is even lower. 18,19 B bigemina therefore infects more cattle as calves because of this higher infection rate in Boophilus microplus compared to B bovis. 18 This was reflected in our study by a tendency for greater odds of endemic stability to B bigemina than B bovis in all decision to leave a few ticks on cows remained a significant term only in the model for anaplasmosis.…”
Section: Relationships Between Tick and Tick Fever Management And Endmentioning
confidence: 99%